Regulating Sharia Financial Transactions: The Role of the Indonesian Ulema Council (MUI) and Implications for Islamic Finance in Indonesia - Muhammad Rais; Harya Pramata (Law and Economics, 2024)
This research examines the role of the Indonesian Ulema Council (MUI) in regulating Sharia financial transactions in Indonesia. The MUI, an independent Islamic advisory body, plays a pivotal role in shaping the regulatory framework for Sharia financial transactions through its issuance of fatwas (religious edicts) and guidelines. The research employs a mixed-methods approach, utilizing both qualitative and quantitative methods, to provide a comprehensive understanding of the MUI's regulatory role. Qualitative methods, such as interviews and document analysis, are used to explore stakeholders' perspectives and the practical application of the MUI's regulatory measures. Quantitative methods, including surveys and data analysis, provide statistical evidence and broader trends, complementing the qualitative findings. The integration of qualitative and quantitative data allows for a nuanced understanding of the MUI's regulatory role and its implications for the Sharia finance industry in Indonesia. The research findings highlight the crucial role played by the MUI in shaping the regulatory framework for Sharia financial transactions. The MUI's fatwas and guidelines provide clarity and direction to financial institutions and businesses, ensuring that they adhere to Sharia principles and ethical standards. The research also underscores the importance of the MUI's collaboration with governmental and regulatory bodies in developing and refining policies and regulations governing Islamic finance.